HEAT EXTRACTION DEVELOPMENT FOR CAR VENTILATION SYSTEM USING ARDUINO BOARD - SANUSI, AMIRAH AIFA (IRC, 2019)
The increment of ambient temperature delivers by hot weather made the vehicle's compartment gain the warmth from the surrounding and the daylight radiation, while inside the compartment will have a higher temperature compared to the ambient temperature. The heat trapped in the confined compartment in the car caused the driver and passengers feel uncomfortable and suffocation when they entered the parked car under sunlight. A car ventilation system using solar energy is designed to decrease the temperature and ventilate the heat out from the parked car during daylight. This project attempts to discuss in designing car ventilation system using a ventilation fan to cool down the temperature inside the car measured by a sensitive temperature sensor. One method is proposed in designing ventilation system using the Arduino board. The method includes the management, control of the cooling circuitry system, measurement, display and comparison in the presence of the system in the prototype car. The result obtained shown that the temperature is reduced by 3°C with the presence of the system in the prototype car. As a conclusion, the model of the ventilation system is effectively working with the ventilation fan and powered by the solar energy.